Pengaruh Perencanaan Pajak Dan Profitabilitas Terhadap Manajemen Laba - Veronica Simanjuntak, Ratna; Oktafiyani, Melati; Indah Hernawati, Retno; Hadi Saputra, Dian Festiana (Universitas Dian Nuswantoro, 2024)
This research aims to determine the influence of tax planning and profitability on the earnings management of the transportation and logistics sector listed on the Indonesia Stock Exchange in 2017–2022. This study falls into the category of quantitative research. Purposive sampling was the method used for the sampling process. Thus, six companies in the transportation and logistics industry made up the sample. Documentation is the method of data collection that is employed. SPSS version 24 software was used to perform the data analysis for multiple linear regression. The results of this study reveal that tax planning has no effect on earnings management. while profitability has an effect on earnings management..